Synthesis and Antibacterial Activity of Some Transition Metal Complexes of Oxime, Semicarbazone and Phenylhydrazone - M. HANIA, MAJED (Asian Journal of Chemistry, 2010)
Co, Ni and Cu complexes have been prepared by reacting metal chloride with 2-formylthiophene oxime, 2-formylthiophene semicarbazone and 2-formylthiophene phenylhydrazone and their antibacterial activity have been studied and compared with their ligands against P. aeruginosa which gave significant results of activity.